THE RELATIONSHIP BETWEEN STUDENTS’ MOTIVATION AND TECHNOLOGICAL CREATIVITY - Sharipova Gulshoda Bahriddinovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the relationship between students’ motivation and their technological creativity. Motivation plays a critical role in fostering innovative thinking and the effective use of technological tools. The study highlights that higher levels of intrinsic and extrinsic motivation lead to increased engagement, experimentation, and creative problem-solving in technology-based tasks. Understanding this connection allows educators to design learning environments that encourage both motivation and the development of technological creativity.